Black grape extract supplementation attenuates blood oxidative stress in response to acute exercise - Skarpanska-Stejnborn, A.; Basta, P.; Pilaczynska-Szczesniak, L.; Horoszkiewicz-Hassan, M. (Biology of Sport, 2010)
The flavonoid-rich active compound in grapes is claimed to be one of the most important natural products. Hence, the objective of our research was to study parameters of the prooxidative-antioxidative balance in athletes supplied with Panace-Vid 2000® preparation consisting of black wine grape extract (Vitis vinifera). The study was carried out on 22 male rowers. The subjects from the supplemented group (n=10) were given one gelatin capsule containing Panace-Vid 2000® three times a day, for six weeks, while the control group (n=12) was given placebo. Before and after the supplementation period, the athletes performed a physical exercise test on the rowing ergometer; varying between 40 and 90% of maximal aerobic power. Each 3-min exercise session was followed by thirty seconds of rest. Blood was sampled from the rowers before the exercise test, one minute after its completion, and after a 24-h recovery period. The activity of antioxidative enzymes (superoxide dismutase, glutathione peroxidase) was determined and the concentration of thiobarbituric acid-reactive substances was measured in the hemolysate of red blood cells. The Total Antioxidant Capacity was determined in the blood plasma. The concentration of lactic acid was measured in the whole blood. An analysis of the results revealed that the supply of grape extract, in the form of Panace-Vid 2000® preparation, contributed to a significant increase in plasma antioxidative capacity and to an insignificant increase in superoxide dismutase, as well as a lower activity of glutathione peroxidase and reduced concentration of lipid peroxidation product levels.